The anticarcinogenic properties of manuka honey - a literature review - Adrianna Muciek; Martyna Mocarska; Anna Orłowska; Katarzyna Strakowska; Laura Opalska; Anna Maryńczak; Jan Mencel; Nicole Nitschke (Quality in Sport)
Background: Since antiquity, honey has been recognised for its healing and antibacterial properties. Recently, Manuka honey (MH) has been identified as possessing antioxidant, anti-inflammatory, antimutagenic, and anticarcinogenic effects.